2011
DOI: 10.3758/s13415-011-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Working memory load reduces the late positive potential and this effect is attenuated with increasing anxiety

Abstract: Emotion regulation decreases the processing of arousing stimuli, as indexed by the late positive potential (LPP), an electrocortical component that varies in amplitude with emotional arousal. Emotion regulation increases activity in the prefrontal areas associated with cognitive control, including the dosolateral prefrontal cortex (DLPFC). The present study manipulated working memory load, known to activate the DLPFC, and recorded the LPP elicited by aversive and neutral IAPS pictures presented during the rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

29
111
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 82 publications
(113 reference statements)
29
111
7
1
Order By: Relevance
“…Studies in this area have shown that increasing mnemonic demands lead to decrements in the magnitude of the activation in functional magnetic resonance imaging (fMRI), and in the latency and amplitude of the event-related N170 component (Gazzaley, 2011;Gazzaley, Cooney, McEvoy, Knight, & D'Esposito, 2005). In addition, late positive ERPs have been found to be sensitive to both WM load and the emotional content of the stimuli, where these two elements exert opposite effects on the attention paid to distracting stimuli (MacNamara, Ferri, & Hajcak, 2011), thus emphasizing the urgent need to clarify their functional interplay.…”
mentioning
confidence: 99%
“…Studies in this area have shown that increasing mnemonic demands lead to decrements in the magnitude of the activation in functional magnetic resonance imaging (fMRI), and in the latency and amplitude of the event-related N170 component (Gazzaley, 2011;Gazzaley, Cooney, McEvoy, Knight, & D'Esposito, 2005). In addition, late positive ERPs have been found to be sensitive to both WM load and the emotional content of the stimuli, where these two elements exert opposite effects on the attention paid to distracting stimuli (MacNamara, Ferri, & Hajcak, 2011), thus emphasizing the urgent need to clarify their functional interplay.…”
mentioning
confidence: 99%
“…The LPP was even eliminated when faces were shown at fixation and participants performed a simple one-back task on the bars to the left and right of the faces (Holmes et al, 2006). Further, the EPN and LPP responses to arousing, emotional pictures from the International Affective Picture Set (IAPS; Lang, Bradley, & Cuthbert, 2008) were eliminated if these pictures were shown in the periphery and were unattended (De Cesarei et al, 2009;MacNamara & Hajcak, 2009, 2010. Last, when IAPS pictures were shown in large format (40°visual angle) and spatial attention was directed to neutral areas within the pictures, emotional effects on the LPP were eliminated Hajcak, Dunning, & Foti, 2009).…”
mentioning
confidence: 99%
“…Several ERP studies have suggested that EPN and LPP to emotional versus neutral pictures are eliminated when pictures are spatially unattended (De Cesarei, Codispoti, & Schupp, 2009;Eimer, Holmes, & McGlone, 2003;Holmes, Kiss, & Eimer, 2006;Holmes, Vuilleumier, & Eimer, 2003;MacNamara & Hajcak, 2009). For example, when each trial showed a vertical pair of faces and a horizontal pair of houses (or vice versa) (cf.…”
mentioning
confidence: 99%
“…In their fMRI study, Gray et al found that the LPFC was the main cerebral region activated in response to the interaction between a memory task and the emotional valence of the stimulus, which predicted the subjects' behavioural responses. Dolcos, LaBar, and Cabeza (2004) investigated the role of the PFC in memories with an emotional valence and concluded that the ability of emotion (specifically related to emotional arousal) to enhance memory formation is partly mediated by changes in PFC activity (left ventrolateral and dorsolateral PFC) and may involve the amplification of the WM operations mediated by LPFC regions (MacNamara et al, 2011;Mikles, Reuter-Lorenz, Beyer, & Fredrickson, 2008).…”
mentioning
confidence: 99%
“…Models of the processing of emotional information have suggested that a network of interconnected neuroanatomical regions-including the amygdala, hippocampus, thalamus, and PFCoperates to process emotional information and emotional memories (Davis, 1992;LeDoux, Cicchetti, Xagoraris, & Romanski, 1990). This top-down control of the amygdala by the PFC allows for the cognitive modulation of emotional processes by frontal brain structures, and the PFC could be crucial for mechanisms underlying the regulation of emotion, such as the inhibition of emotional information or the regulation of specific control monitoring on interference effects (Hariri et al, 2000;Kalish & Robins, 2006;MacNamara, Ferri, & Hajcak, 2011;Sandrini et al, 2003).…”
mentioning
confidence: 99%